Epidemiological profile of elderly women with burning mouth symptoms - doi:10.5020/18061230.2011.p238 - Maria Vieira de Lima Saintrain; Janaina de Oliveira Braga; Márlio Ximenes Carlos; Maria Cristina Germano Maia (Universidade de Fortaleza, 2012)
Objective: To determine the epidemiological profile of elderly women with burning mouth symptoms. Methods: A cross sectional, quantitative, exploratory and descriptive study conducted in two phases: a) determining the prevalence of burning mouth symptoms among 263 elderly women aged between 60 and 83 years who attended six public municipal community centers in Fortaleza-CE, Brazil, b) defining the epidemiological profile of respondents with burning mouth symptoms, through the variables: self-reported diseases, salivary flow, use of medications, dental prosthesis and oral hygiene habits. Data were organized by the Statistical Package for Social Sciences - SPSS version 15. Results: The prevalence of burning mouth symptoms in the group was 19% (n=50). Of these, 41 (82.0%) reported the manifestation of the symptoms as a scalding sensation. Regarding the occurrence, the most referred sites were: tongue (48%; n=24) and gums (22%; n=11). Among elderly women, 24 (48.0%) had daily symptoms. Regarding self-reported diseases and habits: 80.0% cited cardiovascular diseases, 74.0% (n=37) musculoskeletal illness and 62.0% (n=31) neurological disorders, besides 56.0% (n=28) present reduction of salivary flow; 70.0% (n=35) took medication, 66.0% (n=33) were users of dental prosthesis and 18.0% (n=9) did not brush their teeth. Conclusions: The prevalence of burning mouth symptoms in this group was 19%; scalding sensation was the main manifestation of the symptom and the tongue was the site of major symptomatology. The epidemiological profile of symptomatic elderly was distinguished by self-reported diseases and habits such as cardiovascular, musculoskeletal and neurological disorders, in addition to reduced salivary flow, as well as the use of medications and dental prosthesis.